Diploptene δ13C values from contemporary thermokarst lake sediments show complex spatial variation - Davies, Kimberley; Pancost, R.D.; Edwards, M.E.; Walter Anthony, K.M.; Langdon, P.G.; Torres, L.C. (2016)
Cryospheric changes in northern high latitudes are linked to significant greenhouse gas flux to the atmosphere, for example, methane that originates from organic matter decomposition in thermokarst lakes. The set of pathways that link methane production in sediments, via oxidation in the lake system, to the flux of residual methane to the atmosphere is complex and exhibits temporal and spatial variation. The isotopic signal of bacterial biomarkers (hopanoids, e.g. diploptene) in sediments has been used to identify contemporary ocean-floor methane seeps and, in the geological record, periods of enhanced methane production (e.g. the PETM). The biomarker approach could potentially be used to assess temporal changes in lake emissions through the Holocene via the sedimentary biomarker record. However, there are no data on the consistency of the signal of isotopic depletion in relation to source or on the amount of noise (unexplained variation) in biomarker values from modern lake sediments. We assessed methane oxidation as represented by the isotopic signal of biomarkers from methane oxidising bacteria (MOB) in multiple surface sediment samples in three distinct areas known to emit varying levels of methane in two shallow Alaskan thermokarst lakes. Diploptene was present and had δ13C values lower than -38g‰ in all sediments analysed, suggesting methane oxidation was widespread. However, there was considerable variation in δ13C values within each area. The most 13C-depleted diploptene was found in an area of high methane ebullition in Ace Lake (diploptene δ13C values between -68.2 and -50.1‰). In contrast, significantly higher diploptene δ13C values (between -42.9 and -38.8g‰) were found in an area of methane ebullition in Smith Lake. δ13C values of diploptene between -56.8 and -46.9g‰ were found in the centre of Smith Lake, where ebullition rates are low but diffusive methane efflux occurs. The small-scale heterogeneity of the samples may reflect patchy distribution of substrate and/or MOB within the sediments. The ...